The Development of Solar PV Car to Reduce Carbon Emissions from Transport Sector - Arieffadillah, Moch. Farhan; Kumara, I Nyoman Satya; Divayana, Yoga (Journal of Electrical, Electronics and Informatics, 2021)
Global warming is contributed by human activities in many sectors. The sector that contributes significantly to generating carbon emissions is transportation sector. An effort to reduce carbon emissions is by utilizing PV panels on vehicle’s body surface. This paper reviews the development of vehicle-mounted PV panels around the world. The review covers technical specifications, manufacturer, and function of the PV panel on the vehicle. The objective is to get insight on the current development of vehicle with PV panels. The information presented in this paper is expected to provide updates for stakeholders in the field of renewable energy and land transportation in Indonesia. Also, this information can be used as a reference for further research on vehicle with PV panels both in Indonesia or elsewhere that are developing future environmentally-friendly vehicle. The result is a database consists of 948 vehicle which has solar PV around the body of the vehicle. 936 vehicles or about 99% were made for solar car race and only 1% for commercial and prototype. The solar PV system serves as a main or auxiliary power supply of the vehicle depending on whether they are hybrid or fully electric cars.